Characteristics and dynamics of compressible cavitating flows with special emphasis on compressibility effects. (September 2020) - Wang, Changchang; Wang, Guoyu; Huang, Biao
Highlights: Unsteady sheet/cloud cavitating flows are studied using the compressible cavitation solver developed on OpenFOAM. Cavitation fluid compressibility effects on transient flow structures and dynamics are illustrated. Effects of density variance on velocity divergence are proposed. The physics for the compressibility effects on cavitation vortex dynamics are investigated based on VTE budget analysis. Abstract: The objective of the paper is to investigate the physics involved in the compressible cavitating flows, with emphasis on the compressibility effects. 3-D numerical simulations were conducted on the open source software platform OpenFOAM, using both the native incompressible cavitation solver interPhaseChangeFOAM and implemented compressible cavitation solver, where the cavitation model and turbulence model are kept the same and differences of the two approaches mainly root in the density variances of pure liquid and pure vapor. Results are presented for the transient sheet/cloud cavitating flows around a Clark-Y hydrofoil fixed at attack of angle α =8° at inlet velocity U =10m/s and cavitation number σ =0.8, where both ensemble averaged statistics and transient characteristics are analyzed. Good agreement can be obtained using both the incompressible and compressible approaches when compared with the experiment data. While it is found that compared with the incompressible approach, the compressible approach can predict the unsteady cavitation evolution and cavity shedding frequency better. With the compressibility effects considered, the time averaged void fraction distribution decreases, and the cavity size (i.e. cavitation area) becomes smaller. The re-entrant flow thickness normalized by local cavity thickness predicted by the compressible approach is larger than that by the incompressible approach, indicating that the compressible approach can predict the re-entrant jet dynamics well. The velocity divergence analysis show that compared with that in incompressible approach, where velocity divergence mainly comes from the mass transfer between phases, in compressible approach, the velocity divergence originates from both the cavitation two-phase fluid compressibility and mass transfer, and the fluid density variance dominates in compressible results. Following, the budget analysis of vorticity transport equation (VTE) show that the vortex stretching term dominates the cavitation vortex dynamics. Compressibility effects will significantly increase the dilatation term and decrease baroclinic term by decreasing the misalignment between density gradient and pressure gradient. Finally, the temperature and density variance in different cavitation structures are presented.